“If You Need a Psychiatrist, It’s BAD”: Stigma Associated with Seeking Mental Health Care Among Obstetric Providers in Ghana - Lawrence ER; Parekh BJ; Owusu-Antwi R; Newman N; Russell CB; Beyuo TK; Yeboah M; Oppong SA; Moyer CA (International Journal of Women's Health, 2024)
Emma R Lawrence,1 Bela J Parekh,2 Ruth Owusu-Antwi,3 Noah Newman,2 Colin B Russell,1 Titus K Beyuo,4,5 Michael Yeboah,6 Samuel A Oppong,4,5 Cheryl A Moyer1,7 1Department of Obstetrics and Gynecology, University of Michigan, Ann Arbor, MI, USA; 2University of Michigan Medical School, Ann Arbor, MI, USA; 3Department of Behavioural Sciences, Kwame Nkrumah University of Science and Technology/ Psychiatry Unit, Komfo Anokye Teaching Hospital, Kumasi, Ghana; 4Department of Obstetrics and Gynecology, University of Ghana Medical School, Accra, Ghana; 5Department of Obstetrics and Gynecology, Korle Bu Teaching Hospital, Korle Bu, Accra, Ghana; 6Department of Obstetrics and Gynecology, Komfo Anokye Teaching Hospital, Kumasi, Ghana; 7Department of Learning Health Sciences, University of Michigan, Ann Arbor, MI, USACorrespondence: Ruth Owusu-Antwi, Department of Behavioural Sciences, Kwame Nkrumah University of Science and Technology/ Psychiatry Unit, Komfo Anokye Teaching Hospital, Accra Road, Kumasi, Ashanti Region, Ghana, Tel +233244650245, Email rucha_2001@yahoo.comPurpose: Globally, the COVID-19 pandemic has brought attention to the impact of negative patient outcomes on healthcare providers. In Ghana, obstetric providers regularly face maternal and neonatal mortality, yet limited research has focused on provision of mental health support for these providers. This study sought to understand how obstetric providers viewed seeking mental health support after poor clinical outcomes, with a focus on the role of mental health stigma.Patients and Methods: Participants were 52 obstetric providers (20 obstetrician/gynecologists and 32 midwives) at two tertiary care hospitals in Ghana. Five focus groups, led by a trained facilitator and lasting approximately two hours, were conducted to explore provider experiences and perceptions of support following poor maternal and neonatal outcomes. Discussions were audiotaped and transcribed verbatim, then analyzed qualitatively using grounded theory methodology.Results: Most participants (84.3%, N=43) were finished with training, and 46.2% (N=24) had been in practice more than 10 years. Emerging themes included pervasive stigma associated with seeking mental health care after experiencing poor clinical outcomes, which was derived from two overlapping dimensions. First, societal-level stigma resulted from a cultural norm to keep emotions hidden, and the perception that psychiatry is equated with severe mental illness. Second, provider-level stigma resulted from the belief that healthcare workers should not have mental health problems, a perception that mental health care is acceptable for patients but not for providers, and a fear about lack of confidentiality. Despite many providers acknowledging negative mental health impacts following poor clinical outcomes, these additive layers of stigma limited their willingness to engage in formal mental health care.Conclusion: This study demonstrates that stigma creates significant barriers to acceptance of mental health support among obstetric providers. Interventions to support providers will need to respect provider concerns without reinforcing the stigma associated with seeking mental health care.Keywords: provider burnout, therapy, sub-Saharan Africa, LMIC